Intellectuals, Education and Diffusion of Knowledge in Mexico - Ochoa Bilbao, Luis (Íkala, Revista de Lenguaje y Cultura, 2008)
This article presents a brief overview of the educational role of intellectuals in the Mexican mass media. The main topics are the diffusion of history and culture, political education, and the propagation of science. This article supports the idea that this phenomenon relates to education beyond the classroom, which helps to increase public interest in the aforementioned topics. Received: 07-11-07 / Accepté: 27-02-08 How to reference this article: Ochoa Bilbao, L. (2008). Intelectuales, educación y difusión del conocimiento en México. Íkala. 13(1), pp.65-88.